Knowledge, Attitude, and Practices of Dental Practitioners Regarding Domestic Violence in Pakistan - Muhammad Nasir Saleem MSc (UK); Hina Zafar Raja Msc (UK); Asma Shakoor MSc (UK); Haroon Rashid DPH, MPH, MBA, MSc, CMT; Haiqa Nasir BDS; Elyon Yusuf BDS (SAGE Publishing, 2021)
Domestic violence is a complex social issue worldwide that includes a wide range of physical, sexual, psychological, economic, or emotional trauma to a child or adult. A large proportion of domestic violence cases remain unreported or undocumented. Dentists can play an important role in identifying and reporting these cases, but no such local study is available assessing the dental practitioners' attitudes and knowledge of evaluating physical abuse in Pakistan. The objective of this study was to assess the knowledge and practices of dental practitioners of Pakistan about domestic violence. This cross-sectional study was carried out over 2 months, among 330 dentists across Pakistan, selected by convenience sampling technique. Data was collected via a pre-validated online questionnaire, filled anonymously after taking informed consent. The survey questionnaire collected data about dentists' demographics, awareness, and experiences about domestic violence cases via close-ended questions. Only 10.6% of participating dentists received formal training in the management of domestic violence cases. Approximately 55% of participants knew that physical abuse should be reported in all circumstances; however, half of them could not accurately identify the legal authorities where suspected cases should be reported. Only 20% of the participating dentists had ever suspected a case of physical abuse and 30% of those actually reported it to legal authorities. Participants characterized fear of anger from relatives as the most significant barrier toward reporting suspected cases. The analysis revealed that Pakistan's dentists lack adequate knowledge regarding domestic violence in terms of identification, relevant physical signs/symptoms, and social indicators. Dentists of Pakistan had insufficient knowledge about the identification, management, and reporting of domestic violence cases. However, formal training and dentists' qualification were positively associated with overall awareness and practices regarding domestic violence case management.